2018
DOI: 10.3390/f9090564
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Affected Populus simonii Carr. Show Lower Growth and Long-Term Increases in Intrinsic Water-Use Efficiency Prior to Tree Mortality

Abstract: The Three-North Shelter Forest (TNSF) is a critical ecological barrier against sandstorms in northern China, but has shown extensive decline and death in Populus simonii Carr. in the last decade. We investigated the characteristics-tree-ring width, basal area increment (BAI), carbon isotope signature ( 13 C cor ), and intrinsic water-use efficiency (iWUE)-of now-dead, dieback, and non-dieback trees in TNSF shelterbelts of Zhangbei County. Results from the three groups were compared to understand the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 58 publications
(68 reference statements)
4
23
0
Order By: Relevance
“…In this study, we thought the Mongolian pine's death was not related to the dramatic increase of water use efficiency. According to our observation, the Mongolian pine in our research site has already exceeded the extreme drought, considered a more critical factor of the death than the sudden increase of its water use efficiency in response to drought, like in previous studies [23,[44][45][46].…”
Section: Reduced Survival and Growth Of Mongolian Pine Correlates Witsupporting
confidence: 68%
See 3 more Smart Citations
“…In this study, we thought the Mongolian pine's death was not related to the dramatic increase of water use efficiency. According to our observation, the Mongolian pine in our research site has already exceeded the extreme drought, considered a more critical factor of the death than the sudden increase of its water use efficiency in response to drought, like in previous studies [23,[44][45][46].…”
Section: Reduced Survival and Growth Of Mongolian Pine Correlates Witsupporting
confidence: 68%
“…Temporary increases in iWUE help protect trees from drought, but prolonged increases inhibit growth, eventually leading to death [23]. Previous studies have found that intense drought stress significantly increases the risk of death among drought-stressed plants [40,41].…”
Section: Reduced Survival and Growth Of Mongolian Pine Correlates Witmentioning
confidence: 99%
See 2 more Smart Citations
“…in the European Alps. Studies focusing on other species have also reported slower growth rates in declining or dead individuals vs. healthy individuals, serving as a potential early warning signal for tree death [19,21,[62][63][64][65][66]. Particularly for the evergreen Nothofagus dombeyi in Patagonia, Suarez et al [33] found that dead trees during the extreme drought event in 1998-1999 showed lower growth rates 30 years prior to the drought when compared with trees that survived.…”
Section: Discussionmentioning
confidence: 99%